Efficiency Considerations and Application Limits of Single-Phase Active Power Filter with Converters for Photoenergy Applications - Saša Sladić; Srđan Skok; David Nedeljković (International Journal of Photoenergy)
A new way of connecting PV sources to adaptive voltage active power filter (AV APF) has been compared with classic approach including active power filter (APF). In standard active power filter applications a relatively high DC link voltage (500 V or even more) with a buck converter or lower voltage (approx. 100 V) with boost converter can be used. These two converters appear also in adaptive voltage circuit of AV APF, but in this case it is possible to achieve many different connections of DC source. Benefit of this approach is that the same circuit is used for improving switching conditions in APF and for connection of solar cells. It appears that these two functions support each other and a large variety of DC voltages and currents can be connected to AC mains. Experimental results confirm expectations of increased energy transfer from additional DC source to network, especially for DC voltages being lower than DC link voltage.